Recuperação de reservatórios eutrofizados por atividades antrópicas : estudos em microcosmos - Pantano, Glaucia (Universidade Federal de São Carlos, 2016)
The economic development of a country depends on good quality of water available, so the conservation and restoration of water bodies are strategic conditions for this to happen. However, water resources have become scarce over the past decades, in quantitative and qualitative terms. A variety of human activities have caused serious problems to the aquatic environment, and eutrophication is one of the most responsible for the degradation of the quality of water bodies, mainly caused by the artificial enrichment of nutrients, especially phosphorus and nitrogen. There are currently two contrasting scenarios: the excessive presence of phosphorus in aquatic ecosystems and, the depletion of phosphate rock deposits, which endangers the water security and the global food security. In this context the development of technologies aimed at the recovery of the quality of aquatic ecosystems and phosphorus contained in these compartments is of fundamental importance, since the global stock of phosphate rocks is a finite resource and may be close to being exhausted. Various technologies for the remediation of eutrophic environments have been studied, however none of which aims to reuse of phosphorus in agriculture. Thus, the aim of this study was to evaluate the sawdust as biosorbent material to phosphorus aiming the recovery of the quality of water resources and its later use as fertilizer in agriculture. The experiments were conducted in two stages, first were assembled microcosm with water and sediment samples from eutrophic reservoir Ibirité/MG, the total incubation time was 159 days, in this time various parameters (physicochemical and chemical) were monitored in the water column, interstitial water and sediment. After the end of this first experiment arose any question about the phosphorus adsorption in sawdust, what motivated the development of a new experiment with samples of the Barra Bonita/SP. This experiment was performed with sterile and non-sterile samples as well as that had or not a previous addition of iron in the sawdust, the incubation time was 240 and 247 days, respectively for non-sterile and sterile experiment. The results of the first experiment (Ibirité) showed that there was a reduction of 90.5% of orthophosphate in the water column of the microcosms and sawdust adsorbed 16.2 μg g-1, this adsorption occurred mostly after 113 days of incubation. In the second experiment results showed that prior to addition of iron not conducive to increased adsorption in the non-sterile experiments, and the main adsorption mechanism may be not via the action of bacteria oxidizing Fe (II). The higher adsorption in the second experiment took place in sterile microcosm, where sawdust adsorbed 66.9 μg g-1 in the period of 247 days. Knowing that the success in the recovery of water bodies depends on the reduction of external phosphorus sources, the studied technology has a good potential application as a remediation technique and phosphorus reuse as fertilizer, mainly because it is an inexpensive technique and easy to use.
Restoration of reservoirs impacted by anthropic activities : studies in microcosms
Keywords: Remediação; Eutrofização; Serragem; Fósforo; Microcosmos; Remediation; Eutrophication; Sawdust; Phosphorus; Microcosms; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA